Out-of-plane Testing Procedure for Inverse Identification Purpose: Application in Sheet Metal Plasticity - T. Pottier (2018)
Many recent works in inverse identification of constitutive parameters have pointed to the need of tests which exhibit heterogeneous strain paths. The present study details a new testing procedure based on out-of-plane motion capture by Stereo-Image Correlation (SIC). With the original test proposed hereby, a unique sample is deformed on a tensile machine along two perpendicular tensile directions, two perpendicular shear directions and one expansion area. The choice of the sample shape is discussed along with the stereo imaging device, 3D reconstruction and measurement uncertainties. The test sample is made from a sheet of commercially pure titanium. A Finite-Element updating inverse method is applied in order to identify six parameters of an anisotropic plastic constitutive model. Results show that this new testing procedure allows every constitutive parameter of the model to be identified from one and only one test. © 2011 Society for Experimental Mechanics.